2020
DOI: 10.1021/acsomega.0c02132
|View full text |Cite|
|
Sign up to set email alerts
|

Partial Pressure Assisted Growth of Single-Layer Graphene Grown by Low-Pressure Chemical Vapor Deposition: Implications for High-Performance Graphene FET Devices

Abstract: An attempt has been made to understand the thermodynamic mechanism study of the low-pressure chemical vapor deposition (LPCVD) process during single-layer graphene (SLG) growth as it is the most debatable part of the CVD process. The intensive studies are being carried out worldwide to enhance the quality of LPCVD-grown graphene up to the level of mechanically exfoliated SLG. The mechanism and processes have been discussed earlier by several research groups during the variation in different parameters. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…35,36 In addition, pure Cu(111) catalyst has been widely used to grow graphene. 24,[50][51][52] The high density of surface atoms on Cu(111) induces a high carbon atom diffusion rate, promoting a high graphene growth rate. 50 The Cu(111) surface also has a lattice constant similar to graphene, resulting in a low lattice mismatch.…”
Section: Structure Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…35,36 In addition, pure Cu(111) catalyst has been widely used to grow graphene. 24,[50][51][52] The high density of surface atoms on Cu(111) induces a high carbon atom diffusion rate, promoting a high graphene growth rate. 50 The Cu(111) surface also has a lattice constant similar to graphene, resulting in a low lattice mismatch.…”
Section: Structure Modelsmentioning
confidence: 99%
“…79 Experimental results have also shown that it is difficult to diffuse a carbon monomer into the Cu catalyst because of its low carbon solubility. 21,24 In addition, the Cu-Ni-1 catalyst behaves similarly to the Cu catalyst because the atomic fraction of Ni is low, but the adsorption energy difference between the surface and first subsurface is insignificant. The Cu-Ni-2 and Cu-Ni-3 catalysts behave differently from the Cu and Cu-Ni-1 catalysts: the adsorption on the subsurface is more stable than surface adsorption.…”
Section: Adsorption Of Carbon Monomers On the Catalyst Subsurfacementioning
confidence: 99%
See 3 more Smart Citations